D-Serine Ameliorates Neonatal PolyI:C Treatment-Induced Emotional and Cognitive Impairments in Adult Mice - Taku Nagai; Jinghua Yu; Yuko Kitahara; Toshitaka Nabeshima; Kiyofumi Yamada (Elsevier, 2012)
Polyriboinosinic-polyribocytidilic acid (polyI:C) is a synthetic analog that elicits viral-like immune responses in mammals. We have recently found that polyI:C treatment in neonatal mice induced abnormalities of emotional, cognitive, and sensorimotor gating and dysfunction of glutamatergic neurotransmission in adulthood. In this study, we investigated the effect of the NMDA-receptor co-agonist d-serine on polyI:C-induced behavioral abnormalities in mice. Neonatal ICR mice were repeatedly injected with polyI:C for 5 days from postnatal day 2 to 6. At 10 weeks, sensorimotor gating function was analyzed in the prepulse inhibition (PPI) test. Emotional function was analyzed in open field and social interaction tests. Cognitive function was analyzed by novel object recognition tests. d-Serine dose-dependently improved polyI:C-induced impairment of emotional and cognitive behaviors whereas it had no effect on PPI deficit in adults. The ameliorating effects of d-serine were antagonized by pretreatment with an NMDA-receptor antagonist, MK-801. Although the mRNA level of d-amino acid oxidase (DAAO) was increased in the prefrontal cortex and hippocampus of neonatal polyI:C-treated mice in adulthood, no changes were observed in d-serine content and DAAO enzymatic activity. These results suggest that d-serine ameliorates emotional and cognitive impairments of the polyI:C-treated mice through potentiating NMDA receptor activity. Keywords:: cognition, emotion, d-serine, polyI:C, d-amino acid oxidase